ANALISIS KEPEMIMPINAN TRANSFORMASIONAL DALAM PERSPEKTIF KEPEMIMPINAN KRISTEN: STUDI KUALITATIF TERHADAP FILM HACKSAW RIDGE - Pebiana Reski (CV. ADIBA AISHA AMIRA, 2026)
This study aims to analyze transformational leadership from a Christian leadership perspective through a qualitative study of the film Hacksaw Ridge. The method uses content analysis of scenes and dialogues. The findings show that the main character, Desmond Doss, represents the four dimensions of transformational leadership: idealized influence, inspirational motivation, intellectual stimulation, and individualized consideration. In addition, Christian leadership values such as love, service, humility, sacrifice, and faith are strongly reflected. This study finds an integration between transformational and Christian leadership, forming a holistic and value-based leadership model.